On decay and blow-up of solutions for a nonlinear Petrovsky system with conical degeneration - Jiali Yu; Yadong Shang; Huafei Di (Boundary Value Problems, 2020)
Abstract This paper deals with a class of Petrovsky system with nonlinear damping w t t + Δ B 2 w − k 2 Δ B w t + a w t | w t | m − 2 = b w | w | p − 2 $$\begin{aligned} w_{tt}+Δ _{\mathbb{B}}^{2}w-k_{2} Δ _{\mathbb{B}}w_{t}+aw_{t} \vert w_{t} \vert ^{m-2}=bw \vert w \vert ^{p-2} \end{aligned}$$ on a manifold with conical singularity, where Δ B $Δ _{\mathbb{B}}$ is a Fuchsian-type Laplace operator with totally characteristic degeneracy on the boundary x 1 = 0 $x_{1}=0$ . We first prove the global existence of solutions under conditions without relation between m and p, and establish an exponential decay rate. Furthermore, we obtain a finite time blow-up result for local solutions with low initial energy E ( 0 ) < d $E(0)< d$ .